Results from a Phase 1/2 trial of BB2603, a terbinafine‐based topical nano‐formulation, in onychomycosis and tinea pedis. Issue 6 (20th May 2022) - Fuhr, Rainard; Cook, David; Ridden, John; Nield, Kerry; Leigh, Emma; Cook, Julie; Davies‐Strickleton, Heather; Dobmeyer, Juergen
Abstract: BB2603 is a nano‐formulation of the antifungal drug terbinafine with the polymer polyhexamethylene biguanide (PHMB) as an excipient to enhance solubility and drug delivery to skin and nails. BB2603 is delivered topically using a low‐velocity spray. It is being developed in different strength formulations for the treatment of fungal infections of the nail and skin, including onychomycosis and tinea pedis, with BB2603‐1 (0.01% terbinafine) tested in the present trial. The aim of this study was to assess systemic exposure, safety and tolerability of BB2603‐1 compared with Lamisil ® AT 1% spray and BB2603‐1 vehicle control in onychomycosis and tinea pedis. Preliminary mycological and clinical activity were also investigated. This was a single‐centre Phase 1/2, randomised, partially blinded, active‐ and vehicle‐controlled, parallel‐group trial in 46 subjects with onychomycosis associated with tinea pedis. Part 1 investigated BB2603‐1 versus Lamisil AT 1% spray and BB2603‐1 vehicle (4 weeks treatment). Part 2 investigated BB2603‐1 versus BB2603‐1 vehicle (additional 48 weeks treatment). No measurable systemic exposure of terbinafine was shown over 52 weeks of treatment with BB2603‐1. BB2603‐1 had an excellent safety and tolerability profile with no drug‐related safety findings and no evidence of skin sensitisation. BB2603‐1 showed preliminary evidence of anti‐dermatophyte activity, demonstrated by a reduction in dermatophyte positive cultures and a reduction in microscopic evidence of dermatophytes. The pharmacokinetic, safety and efficacy data from this trial support further development of the topical terbinafine‐based nano‐formulation BB2603 in fungal infections of the skin and nail, including onychomycosis and tinea pedis.